Pelaksanaan Diversi Terhadap Anak Pelaku Tindak Pidana di Tinjau dari Undang–Undang Nomor II Tahun 2012 Tentang Sistem Peradilan Pidana Anak (Studi Kasus Penetapan Pengadilan Negeri Jakarta Pusat Nomor: 01/Pid.Sus-Anak/Div/2021/PN JKT PST) - Jubaedah, Ratna (Jurnal Kewarganegaraan, 2022)
Diversion is the transfer of the settlement of children's cases from the criminal justice process to a process outside of criminal justice. With the implementation of diversion, the case will not be tried, the implementation of this diversion uses a system of consensus or deliberation, not all cases of children can be diverted, cases that can be diverted only with threats under 7 years old in accordance with article 7 paragraph 2 of Law number 11 years 2012 regarding the implementation of diversion. If the diversion fails at the police department, it will continue to the prosecutor's stage, if the diversion at the prosecutor's office still fails, it will be carried out in court, if in court it still fails, it will proceed to the trial stage. Regulation of the Supreme Court (PERMA) Number 4 of 2014 concerning Guidelines for Implementing Diversion in the Juvenile Criminal Justice System in court: 1. Determination of Deliberation 2. Minutes of Diversion 3. Agreement 4. Report of Agreement Results 5. Appointment of Judges 6. Appointment of the Chief Justice of the Court of Legal Consequences Implementation of Diversion, if the child fails to make diversion efforts, it will proceed to the trial stage and will follow the guidance if the diversion is successful then the child will not follow the social guidance. This study uses a normative juridical and empirical juridical approach. Data was collected by means of literature studies and field studies. Data analysis was carried out qualitatively. Based on the results of the study, it can be concluded that the implementation of diversion against children. Perpetrators of criminal acts in terms of Law Number II of 2012 article 7 paragraph (1) at the level of investigation, prosecution and examination of children's cases in the District Court must seek diversion.